Effect of Virtual Reality in 360 degrees Video to Improve Standard Precautions Compliance amongst Nursing Students - Triyanto, Endang; Kusumawardani, Lita Heni; Jauhar, Muhamad; Rasdiyanah, Rasdiyanah; Rohana, I Gusti Ayu Putu Desy; Rachmawati, Utami (Jurnal Keperawatan Soedirman, 2024)
Nursing students need effective learning methods to improve their abilities and skills in achieving competency. Virtual care reality in 360o videos is an alternative solution to a real and concrete learning method. This study aims to determine the effect of virtual care reality in 360o (VCR 360o) videos on compliance with standard precautions in nursing professional students. The study used a randomized control trial with the sample of 32 students for each group was obtained through a random sampling technique. This research was conducted at two state universities in Indonesia in 2022 and provided an intervention in the form of a 360o VCR for 17 minutes at least three times in each video containing material on standard precautions. A standard precautions compliance questionnaire was employed to investigate the main variable with a further analysis using paired t-test and independent t-test. The results of the study showed that there was a significant effect of the VCR 360o on increasing standard precautions compliance among students (p = 0.004). The research results are expected to be applied in the learning process of nurses in tertiary institutions and other learning topics.